Kompleksnaja pedagogiceskaja ocenka rabotosposobnosti kvalificirovannych plovcov-podvodnikov v mikro- i mezocikle - Miasnikova, T. I. (Uchenye zapiski universiteta imeni P.F. Lesgafta, 2019)
The complex indicators characterizing the level of the athlete`s performance are necessary to assess the effectiveness of the previous stage and control the condition. The sports practice needed simple reliable and informative methods to assess performance. The results of the qualified finswimmers were used when performing the loads of different zone tests and the indicator "sum of three pulses" for substantiating the complex assessment. The criteria of the complex pedagogical assessment of the working capacity of the qualified finswimmers are allocated; also, the characteristic of the levels of working capacity is given. The practical importance of the comprehensive pedagogical assessment of performance is the availability and possibility to use it for the control in the training of the qualified finswimmers.